2017
DOI: 10.1097/coc.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy (SBRT) Combined With Chemotherapy for Unresected Pancreatic Adenocarcinoma

Abstract: Introduction The role of conventionally fractionated radiation therapy in the management of unresectable pancreatic cancer is controversial. One concern about concurrent chemoradiation relates to the timing of chemotherapy. In contrast to conventional radiation therapy, SBRT delivers high doses in a shorter duration resulting in minimal disruption in chemotherapy. Here we report our results of patients treated with SBRT and chemotherapy for inoperable pancreatic cancer. Methods Thirty-eight consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 36 publications
(38 reference statements)
2
35
0
Order By: Relevance
“…A retrospective series by Gurka et al, 35 including 38 patients with locally advanced, borderline resectable, and medically inoperable pancreatic cancer treated with SBRT and gemcitabine or folinic acid, fluorouracil, and oxaliplatin (modified FOLFOX), revealed a median overall survival of 14.3 months. 35 A subsequent study by Moningi et al 36 evaluating patients with borderline resectable and locally advanced pancreatic cancer showed similar results with a median survival of 13.9 months. Similarly, a multi-institutional phase 2 study of 49 patients with locally advanced pancreatic cancer treated with gemcitabine followed by SBRT also demonstrated a median overall survival of 13.9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective series by Gurka et al, 35 including 38 patients with locally advanced, borderline resectable, and medically inoperable pancreatic cancer treated with SBRT and gemcitabine or folinic acid, fluorouracil, and oxaliplatin (modified FOLFOX), revealed a median overall survival of 14.3 months. 35 A subsequent study by Moningi et al 36 evaluating patients with borderline resectable and locally advanced pancreatic cancer showed similar results with a median survival of 13.9 months. Similarly, a multi-institutional phase 2 study of 49 patients with locally advanced pancreatic cancer treated with gemcitabine followed by SBRT also demonstrated a median overall survival of 13.9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with metastatic disease at diagnosis (n 5 85,653) or surgery of the primary site (n 5 42,794) were excluded. Patients who underwent resection were identified according to the Facility Oncology Registry Data Standards surgery codes: 25,30,35,36,37,40,60,70,80, and 90. The cohort was further restricted by the sequential exclusion of patients who did not receive any treatment at the reporting facility (n 5 13,659), were diagnosed with other malignancies (n 5 11,501), or did not receive chemotherapy (n 5 22,417) as well as those whose radiation treatment included electrons and/or neutrons (n 5 54), proton therapy (n 5 43), or radioisotopes (n 5 11) or who started treatment more than 90 days after their diagnosis (n 5 1222).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Iacobuzio-Donahue et al 5 demonstrated up to 30% of pancreatic cancer patients died from locally obstructive disease with few or no distant metastases. These findings highlight the potential benefit 14 20 LA 25 Gy 9 1 94 11.8 1c induction + post-SBRT GEM Goyal et al 15 19 LA/LR 20-25 Gy 9 1, 8-10 Gy 9 3 81 14.4 5-FU or GEM Lominska et al 16 28 LA/LR 4-8 Gy 9 3-5 86 5.9 5-FU or GEM prior to SBRT Chuong et al 17 73 BR/LA 5-10 Gy 9 5 81 16.4 BR, 15 LA 3 cycles GTX Gurka et al 18 38 BR/LA 5-6 Gy 9 5 79 12.3 Post/concurrent-GEM or 5-FU Moningi et al 19 88 BR/LA 5-6.6 Gy 9 5 61 18.4 Peri-SBRT GEM or 5-FU Herman et al 20 49 LA 6.5 Gy 9 5 78 13.9…”
Section: Discussionmentioning
confidence: 99%
“…In recent years SBRT has emerged as an effective treatment option for a variety of malignancies including early stage lung cancer, prostate cancer, and pancreatic cancer (24)(25)(26). SBRT represents a novel means of delivering highly conformal ultra-high dose hypofractionated radiation therapy.…”
Section: Rationale For Sbrtmentioning
confidence: 99%